Mechanism of Pd(OAc)2/Pyridine Catalyst Reoxidation by O2: Influence of Labile Monodentate Ligands and Identification of a Biomimetic Mechanism for O2 Activation - Popp, Brian V.; Stahl, Shannon S. (Chemistry : a European journal, 2009)
Aerobic oxidation: Mechanisms of aerobic oxidation of the PdII(OAc)2/pyridine catalyst system were evaluated by using density functional theory methods. The results reveal that labile monodentate ligands, such as pyridine, favor a catalyst reoxidation pathway that proceeds via Pd0, rather than direct reaction of O2 with a PdII–hydride intermediate (see scheme). The mechanism of catalyst oxidation by O2 in Pd‐catalyzed aerobic oxidation reactions has been the subject of considerable debate, particularly with respect to the reactivity of PdII–hydride species. Here, we describe the use of unrestricted DFT computational methods to investigate the mechanism of catalyst reoxidation with the Pd(OAc)2/pyridine catalyst system, one of the most widely used catalysts. These studies probe four different pathways for the formation of a PdII–hydroperoxide species from the reaction of O2 from the corresponding PdII–hydride [(py)nPdII(H)OAc]: 1) a homolytic pathway involving hydrogen‐atom ion by O2; 2) AcOH reductive elimination to yield a Pd0 species that subsequently reacts with O2; 3) migratory insertion of O2 into a PdH bond; and 4) oxidative addition of O2 to PdII to yield a PdIV(η2‐peroxo) species. In contrast to previous studies of reactions between O2 and Pd–hydride species, the reductive‐elimination pathway (mechanism 2) is significantly more favorable than any of the other pathways. This outcome is traced to the presence of labile ligands (pyridine) that can readily dissociate from Pd to enable the hydride and acetate ligands to occupy cis‐coordination sites. These results strongly support the involvement of Pd0 as an intermediate in the catalytic cycle. Investigations of the mechanism of the reaction of O2 with the Pd0 intermediate revealed a novel, previously unrecognized mechanism that yields a Pd–OOH product without proceeding through the intermediacy of a PdII(η2‐peroxo) species. This mechanism resembles pathways commonly observed in biological O2 activation and suggests that noble‐metal and biological oxidation mechanisms may be more similar than previously appreciated. Aerobic oxidation: Mechanisms of aerobic oxidation of the PdII(OAc)2/pyridine catalyst system were evaluated by using density functional theory methods. The results reveal that labile monodentate ligands, such as pyridine, favor a catalyst reoxidation pathway that proceeds via Pd0, rather than direct reaction of O2 with a PdII–hydride intermediate (see scheme).